Companies that Promote Empowerment - Magdalena BOROWSKA; Agata PIETRON-PYSZCZEK (Communications of International Proceedings, 2021)
The aim of this study is to determine the scope of application of empowerment in enterprises operating in the Polish market. Based on the literature review, it was assumed that empowerment, viewed as granting power to employees, may have different intensity, which is reflected in the division into seven levels of empowerment. Characterization of these levels was presented in an online survey addressed to employees of enterprises diversified in terms of their business profile (production, trade, services), organizational status (independent entity, branch/department of the corporation), the origin of capital (domestic, foreign), employment size, and the time the enterprise operates in the market. Respondents replied whether their enterprises use purposeful managerial actions and practices which, by increasing independence and autonomy, increase the status and authority of employees, and indicated the level of empowerment which, in their opinion, is dominant.
Keywords: Empowerment; Employees; Employee Interests.